Analysis Of The Implementation Of Collaborative Learning In Islamic Religious Education Learning For The Development Of Social And Spiritual Competencies - Ria Minhatullaili Ria Minhatullaili (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This research is motivated by the importance of developing social and spiritual competencies in Islamic Religious Education (PAI) learning amidst the challenges of 21st-century education that emphasizes not only cognitive aspects but also the formation of students' character. PAI learning practices in various schools still tend to be teacher-centered and memorization-oriented, so that the development of social and spiritual aspects is not optimal. This study aims to analyze the implementation of collaborative learning in PAI learning and its contribution to the development of students' social and spiritual competencies. The study used the Systematic Literature Review (SLR) method with a qualitative synthesis approach to 28 articles obtained from the Google Scholar, Scopus, DOAJ, and Moraref databases in the period 2015–2025. Data were analyzed through thematic coding and content analysis to identify patterns of findings related to social competencies, spiritual competencies, and the integration of Islamic values in collaborative learning. The results showed that collaborative learning can improve students' communication skills, cooperation, tolerance, empathy, and social responsibility through discussion activities and group work. Moreover, collaborative learning also supports the internalization of spiritual values such as honesty, social awareness, moral responsibility, and Islamic ethics through reflective and participatory social interactions. This study concludes that collaborative learning is a relevant learning approach for creating more interactive, humanistic Islamic Religious Education (PAI) learning, oriented toward the integrated development of students' socio-spiritual character